ANALISA KEBOCORAN FUEL SUPPLY PUMP PADA UNIT EXCAVATOR PC 135F-10M0 DI PT XYZ - Marali, Aryati Muhaymin; Muhaimin, Muhamad; Arwin, Arwin; Dwimas, Herdia; Yusrina, Yasmin Zulfati; Ulum, Muhammad Showi Nailul (Politeknik Negeri Semarang, 2025)
The fuel system utilized in a unit is a crucial system, serving as the fuel supplier to the unit to start the engine. If the engine fails to start, one possible cause is a malfunctioning or damaged component of the fuel system, resulting in the high-pressure fuel not reaching the common rail. Consequently, the fuel is not supplied to the high-pressure common rail, leaving the engine without the required fuel supply. The outcome of this research is to identify and analyze the cause of the fuel supply pump component leakage in the excavator PC 135F-10M0 unit, with symptoms of the return hose to the tank being trapped by a clamp. Careless operation led to a wooden rod protruding into the bottom cover of the unit, puncturing and affecting the clamp on the fuel return hose to the tank.